Analysis Of MSME District In Cileungsi District-Bogor Regency Using K-Means Cluster - Ariwibowo, Prasetio; Purba, Indra Setiawan; Fiyanto, Ary (Universitas 17 Agustus 1945, 2025)
The purpose of this research is for MSME actors and the local government to provide solutions for limited capital, limited professional human resources, and limited access to information in order to measure market opportunities for both the government of Bogor Regency and MSME actors in Cileungsi District, Bogor Regency. The quantitative data used is secondary data, namely MSME actors in Cileungsi District, Bogor Regency and data obtained from the Office of Cooperatives and Small and Medium Enterprises of Bogor Regency. The data analysis method used is the K-Means and Clustering method. This study is based on the researchers' ideas supported by secondary data used as the basis for determining the MSME Clusters in Cileungsi District, Bogor Regency. The result of this study is that it groups Micro, Small, and Medium Enterprises (MSMEs) in Cileungsi District, Bogor Regency into 3 clusters using the K-means clustering method. The result of this study is that it classifies Micro, Small, and Medium Enterprises (MSMEs) in Cileungsi District, Bogor Regency into 3 clusters using the K-means clustering method. The calculations show that Cileungsi Kidul Village is included in cluster 1, which is the high cluster, Cileungsi Village is in cluster 2, which is the medium cluster, and Cipenjo Village, Cipeucang Village, Dayeuh Village, Limus Nunggal Village, Mampir Village, Pasir Angin Village, and Setusari Village are in cluster 3, which is the low cluster. These districts will receive government attention regarding the determination of marketing strategies to develop the market based on the priority levels of each cluster.